DEGRADASI NILAI-NILAI KEARIFAN LOKAL DALIHAN NA TOLU PADA REMAJA DI KOTA PADANGSIDIMPUAN - Cipto Duwi Priyono; Izuddinsyah Siregar (Institut Pendidikan Tapanuli Selatan, 2021)
This research departs from the phenomenon of the decline in the character of adolescents, especially in the millennial generation, which is already very alarming. The purpose of the research was to explore the decline in the values ​​of local wisdom of dalihan na tolu in adolescents in Padangsidimpuan City. The research method used to answer the problems in this study uses a qualitative research method with an analytical descriptive approach. Data analysis was carried out using the technique of Miles and Huberman, namely data analysis was carried out simultaneously starting from data collection, data condensation, data display and drawing conclusions which were carried out continuously during the research process.The research findings produce at least two main things that are discussed in the research, namely; (1). The character values ​​contained in the Dalihan na tolu indigenous local wisdom include; Marmora's respect contained character values; courtesy, gentleness and responsibility, elek maranak boru; found the value of hard work, independent, honest, loyal, disciplined and caring, while the manatmarkahanggi contained values; honest, hardworking, disciplined, democratic, fair and tolerant. While the second is; (2). The decline in the character values ​​of the local wisdom of dalihan na tolu in adolescents in the city of Padangsidimpuan, among others; the loss of the culture of mutual cooperation, tolerance, speech and manners. Teenagers no longer fully recognize the concept of values ​​in the dalihan na tolu adat, such as attitudes towards parents, attitudes towards friends and the conception of dalihan na tolu adat values ​​in social life. The institutional activities of naposo-nauli bulung, which were previously a forum for youth to recognize and understand the traditional culture of dalihan na tolu, are now running out. Even in some areas in the city of Padangsidimpuan, the naposo-nauli Bulung institution no longer exists. The conclusions in this study include (1). The values ​​of dalihan na tolu indigenous local wisdom contain noble character values ​​and are in accordance with the character values ​​of education proclaimed by the current government. (2). The current decline in character values, especially among teenagers in Padangsidimpuan City, has entered an alarming phase, seen in behavior, understanding and actualization of social life, which has deviated far from the noble values ​​of the adat dalihan na tolu in Padangsidimpuan City.